Caught Between Slavery and Precarity in the Agricultural Sector: South Asian Migrant Farm Laborers’ Working Conditions, Health, and Quality of Life in Nea Manolada, Greece - Theodoros Fouskas (Social Sciences, 2026)
The agricultural sector in Greece heavily relies on migrant workers, particularly from South Asian countries, such as Bangladesh, Pakistan, and India. Research has shown that these workers face numerous challenges, including unsanitary living conditions, exposure to hazardous working conditions, harmful chemicals, a lack of safety equipment, accidents, abuse, violence, and exploitative conduct from employers. Drawing on 45 in-depth interviews, this article analyzes the experiences of Bangladeshi migrant farmworkers employed as strawberry pickers in Nea Manolada, Greece. This study specifically examines how precarious and harsh working conditions in the agricultural sector affect the health, quality of life, and social integration of these unskilled workers. Evidence from the empirical sample reveals that Bangladeshi workers experience hazardous working environments, a lack of labor rights and contracts, chronic job insecurity, and exposure to harmful chemicals and are particularly vulnerable to injury, exploitation, and poverty due to the ethnic–racial division of labor, legal uncertainty, threats of deportation, overcrowded and unsanitary housing, poor nutrition, persistent job insecurity, health risks, and limited access to healthcare. These challenges and inequalities, both in employment and health, are seen as situations akin to modern slavery. This study underscores the urgent need for legislative, labor, and public health interventions to address the specific conditions faced by Bangladeshi migrant workers in the agricultural sector. While this research provides an in-depth insight into this group, it also acknowledges limitations regarding gender, sector, and wider representativeness. The results contribute to a nuanced understanding of the intersection between legal status, the ethnic–racial division of labor, working conditions, health, and quality of life among South Asian migrant agricultural workers in Southern Europe.